2010
DOI: 10.5488/cmp.13.13001
|View full text |Cite
|
Sign up to set email alerts
|

Canonical-dissipative limit cycle oscillators with a short-range interaction in phase space

Abstract: We consider limit cycle oscillators in terms of canonical-dissipative systems that exhibit a short-range interaction in velocity and position space as described by the Dirac delta function. We derive analytical expressions for stationary distribution functions in phase space and energy space and propose a numerical simulation scheme for the simulation of the many body system as well. We show that the short-range interaction squeezes or stretches energy distribution functions depending on whether the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, studies in accelerator physics, [26][27][28][29][30] plasma physics, 31 and astrophysics 32,33 can be found that make extensive use of nonlinear Fokker-Planck equations. Nonlinear Markov processes described by nonlinear Fokker-Planck equations, [34][35][36][37][38][39][40][41][42][43] generalized master equations [44][45][46][47] and Boltzmann equations [48][49][50][51] have been studied to address issues of non-extensive thermostatistics [52][53][54] and classical quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies in accelerator physics, [26][27][28][29][30] plasma physics, 31 and astrophysics 32,33 can be found that make extensive use of nonlinear Fokker-Planck equations. Nonlinear Markov processes described by nonlinear Fokker-Planck equations, [34][35][36][37][38][39][40][41][42][43] generalized master equations [44][45][46][47] and Boltzmann equations [48][49][50][51] have been studied to address issues of non-extensive thermostatistics [52][53][54] and classical quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…This form is motivated by the exact form for an ordinary constant-mass Brownian particle in a potential. In our case this ansatz turns out to work for the joint probability density of x and p, but in contrast to the constantmass case [28], it can then not work for the probability density of x andẋ. Inserting the ansatz into (9), we obtain:…”
Section: Analytical Solutionsmentioning
confidence: 69%
“…In order to arrive at a more precise interpretation of the stationary distributions, we may discuss the stationary distribution in appropriately-defined one-dimensional spaces related to the invariants H 1 and H 2 , rather than in the original state space [57][58][59]. That is, we define the distributions:…”
Section: Active Spinning Top Featuring Non-extensive Statistics: An Amentioning
confidence: 99%